2011
DOI: 10.1063/1.3584850
|View full text |Cite
|
Sign up to set email alerts
|

Reversible phase changes in Ge–Au nanoparticles

Abstract: We demonstrate a reversible phase transition in nanoparticles composed of a binary eutectic alloy, Ge–Au. The structure, 9 nm diameter nanoparticles embedded in silica, can be switched from bilobe to mixed using a 30 ns ultraviolet laser pulse. The structure can be switched back to bilobe by heating at 80 °C. The bilobe/mixed switching can be performed on the same sample at least ten times. Synchrotron X-ray diffraction studies reveal that the bilobe structure contains crystalline Ge and Au while the mixed str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…4b), and each RTA step except the first taking an identical initial distribution and thus returning an identical final distribution. This result corresponds with recent experiments [3], which have shown that the process is repeatable in an AuGe alloy nanoparticle system with nanoparticles still present after ten PLM/RTA cycles, and suggests that no significant degradation in the size distribution will occur. It should be noted, however, that this result may be an artifact of the small interface energy; the smaller particle size means the laser is able to "reset" the distribution to a single peak of very small particles, while in a system with higher interface energy, some very large particles may survive the pulse and lead to a different distribution.…”
Section: Annealingsupporting
confidence: 91%
See 2 more Smart Citations
“…4b), and each RTA step except the first taking an identical initial distribution and thus returning an identical final distribution. This result corresponds with recent experiments [3], which have shown that the process is repeatable in an AuGe alloy nanoparticle system with nanoparticles still present after ten PLM/RTA cycles, and suggests that no significant degradation in the size distribution will occur. It should be noted, however, that this result may be an artifact of the small interface energy; the smaller particle size means the laser is able to "reset" the distribution to a single peak of very small particles, while in a system with higher interface energy, some very large particles may survive the pulse and lead to a different distribution.…”
Section: Annealingsupporting
confidence: 91%
“…Just 100 ns after the laser pulse ends, the temperature of the implanted layer has dropped to 589 K, corresponding with experimental evidence of a fast quench rate [3]. Because of the relatively high thermal conductivity of silicon, the highest temperature the substrate reaches is 458 K at the surface.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Low eutectic point in Au 1−x Si x can fabricate easily on the a-Si film [19], a thin film of organic electroluminescence diode [20] and ZnO diode [21]. Other representative applications in nano-engineering, write-once optical disk [22] and rewritable data storage [23] were proposed.…”
Section: Introductionmentioning
confidence: 99%